Physical performance development in a female national team soccer program - Poehling, R.; Manson, S.; Tsai, M. C.; Koehle, M. S.; Meylan, C. M. P. (Journal of Science and Medicine in Sport, 2021)
Objectives: Significant resources are invested in maximizing player performance without extensive knowledge of the athletic progression of elite female soccer players during their career. The aim of the current study was therefore to investigate the change in physical performance characteristics in 12- to 34-year-old female soccer players in a national team program. Design: Mixed-longitudinal study. Methods: Physical performance was assessed across five years and 657 testing occasions (n=143) using anthropometrics, 40 m sprint (10 m split), broad jump, countermovement jump, squat jump, and 30-15 intermittent fitness test (IFT). Results: Using a Gaussian mixture model, Youth and Senior groups were bifurcated at approximately 23 years old. Subsequent linear mixed models for each group and variable identified significant improvements in the Youth group in maximal speed (30-40 m split), broad jump, countermovement jump, and final velocity30-15IFT (p<0.002), and a decrease in squat jump height with increasing age (=0.04). The Senior group recorded slower 10 m sprint time and a decrease in squat jump height with increasing age (p<0.001). Body mass increased from 12 to 34 years old (Youth and Senior: p(0.001). The Youth group significantly differed in the rate of change compared to the Senior group in body mass, 10 m sprint time, countermovement jump, squat jump, and final velocity30-15IFT (p <0.001). Conclusions: This information can be used to identify average rates of physical performance improvement and decay to help guide optimal physical training and maximize the longevity of a female soccer players` career.